ANALISIS MANAJEMEN BISNIS SYARIAH STRATEGI PENJUALAN JASA PERCETAKAN DI KOTA BOGOR DI MASA PANDEMI COVID-19 - Rully Trihantana; Ria Kusumaningrum; Ai Nurjanah (SAHID BUSINESS JOURNAL, 2022)
The printing business is one that feels a dilemma because of the Large-Scale Social Restrictions (PSBB) to reduce the spread of the Corona Virus during a pandemic. If usually the printing shop was filled with visitors, now it looked deserted and only a few customers and employees were on guard. In some areas, a number of small printing shops have started to close and not serve customers. However, some are still open, but only serve online order pickup and delivery. During this pandemic, of course, many people choose to reduce activities outside the home and limit interactions with other people or what is known as social distancing. This method is believed to prevent the spread of the Corona Virus. However, on the other hand, the printing business is trying hard to maintain the continuity of their business in the midst of the epidemic. One of the efforts to maintain a printing business or printing service that has been sluggish and avoid the threat of bankruptcy includes making business pivots and making promotions.